Atlas-based knee osteophyte assessment with ultrasonography and radiography: relationship to arthroscopic degeneration of articular cartilage. (3rd March 2016) - Koski, JM; Kamel, A; Waris, P; Waris, V; Tarkiainen, I; Karvanen, E; Szkudlarek, M; Aydin, SZ; Alasaarela, E; Schmidt, W; De Miguel, E; Mandl, P; et al.
Abstract : Objectives : To investigate intra- and inter-reader agreement of ultrasonography (US) and conventional radiography (CR) for the evaluation of osteophyte presence and size within the tibiofemoral joint. In addition, to correlate these findings with arthroscopic degeneration of the articular cartilage. Method : Forty adult patients with knee pain were enrolled in this study. Knee CR and US scanning of the medial and lateral bone margins were performed on all patients. A novel atlas for the US grading of knee osteophytes was used in the evaluation. The number and size of the osteophytes were evaluated semi-quantitatively in two rounds from both the CR images (four readers) and the US images (14 readers). The Noyes grading system was used for the evaluation of arthroscopic degeneration of the articular cartilage in 26 patients. Results : On average, intra- and inter-reader US and CR agreement was substantial and comparable to each other (κ = 0.60–0.72). US detected more osteophytes than CR at both the medial (65% vs. 48%) and lateral (70% vs. 60%) compartments. A statistically significant correlation between CR- or US-based osteophyte and arthroscopy grades was observed only for US at the medial compartment (rs = 0.747, p < 0.001). Conclusions : The detection of knee osteophytes using the novel US atlas is as reproducible as reading conventional radiographs. US is more sensitive to detect knee osteophytes than CR. Furthermore, osteophytes detected with US correlate significantly with arthroscopic cartilage changes at the medial knee compartment whereas those detected by CR do not.